Effectivity Of Prabayar System Implementation At PT PLN (Persero)ULP NATAR - Riski Sapitri; Khairudin Khairudin; Aminah Aminah (Cita konsultindo, 2024)
The purpose of this study was to determine the effectiveness of implementing a prepaid system, as well as reducing the number of postpaid customer arrears. This research is a qualitative research conducted at PT PLN (Persero) ULP Natar because PT PLN (Persero) ULP Natar as a whole uses quite a lot of electricity, but the use of prepaid system electricity is still not effective in reducing the amount of arrears caused by the postpaid system. The research was conducted by directly interviewing the team leader and office employees. The results showed that the implementation of the prepaid system of PT PLN (Persero) ULP Natar was less successful / less effective. This research provides recommendations to PT. PLN (Persero) ULP Natar on how to priontize this issue to encourage more customers to switch to a prepaid electricity system for consumers in the area. This can be done by engaging clients in programmatic socialization, which includes education about prepaid electricity through campaigns featuring more engaging messages, promoting token top-ups through social media, websites, and banners. In addition, it is important to increase face-to-face interactions with customers to reinforce their beliefs about the benefits of using electricity.